PENGARUH LEADERSHIP DAN EMPLOYEE ENGAGEMENT TERHADAP JOB PERFORMANCE MELALUI JOB SATISFACTION(Pada Sekretariat Daerah Kota Pasuruan) - Khasbullah Khasbullah; Kuncoro Kuncoro; Sodik Sodik (Jurnal Pendidikan Dasar dan Sosial Humaniora, 2022)
This study aims to obtain empirical evidence of leadership abilities and employee engagement in encouraging increased job performance, either directly or through job satisfaction mediation.This type of research is quantitative with the SEM-SmartPLS method. Data were obtained through questionnaires which were distributed to 60 employees of the Pasuruan City Regional Secretariat.Empirical evidence shows that both leadership and employee engagement are able to strongly encourage increased job performance. The mediating role of job satisfaction is also strong, both in mediating the influence of leadership on job performance and on the effect of employee engagement on job performance. This finding is supported by the descriptive of the four variables, all of which received high responses, including superiors who can be good role models for their subordinates and are able to give pride to subordinates, employees already have high sacrifices for the organization, such as doing a good job and being able to do overtime. if needed, employees have received gai in accordance with regional standards and sufficient to meet the needs of the family, and employees often reach the target given by the company